Incorporating knowledge sharing behaviour in a knowledge management system for academic institutions / Alsaleh Saad - Saad, Alsaleh (2015)
This thesis proposed a knowledge management system framework for academic institutions based on academicians' knowledge sharing behaviour. The current knowledge management systems in higher learning institutions do not capture and represent most of the knowledge types in the academic institutions and little attention has been given to human aspects. A qualitative research approaches were employed in this research. This research was carried out in four stages which are: knowledge acquisition; data collection; data analysis and findings; and development of a knowledge management system framework. The research site was at Malaysia's largest academic institution in terms of size and population. The study discovered two types of knowledge shared among academicians; namely: corporate knowledge and social knowledge. The knowledge sharing networks among the academicians include Community of Practice network, Personal network, and Business Club network. The study also identified two main knowledge sharing methods used by academicians to share knowledge which are synchronous and asynchronous. Five knowledge sharing motivations among academicians were identified: building a reputation, acknowledgement, to be knowledgeable, vision and mission, and reciprocity. The study identified three issues that academicians recommended to be considered. These issues are: offer information about experts, manage and categorize contents, and ensure accessibility. This research contributed toward new knowledge through the development of a knowledge management system framework which drew upon qualitative findings. The administrations of universities may utilize the proposed framework as a guide for their KS activities among academicians.